Measurements and modeling of N2-broadening coefficients for the ν6 band of CH3F, comparison with CH3Cl and CH3Br molecules. (December 2017) - Ramchani, A. Barbouchi; Jacquemart, D.; Soulard, P.; Guinet, M.
Highlights: Fourier transform spectroscopy of the ν6 band of methyl fluoride at room temperature. N2 -broadening coefficients for 899 transitions. Comparison between our measurements and calculations with those from literature. Comparison of N2 -broadening coefficients with CH3 Br and CH3 Cl molecules. Abstract: The 8.5-µm spectral region of methyl fluoride was recently studied in terms of line positions, intensities and self-broadening coefficients at room temperature [JQSRT 2016;185:58–69]. The present work is dedicated to measurements of N2 -broadening coefficients for transitions of the ν6 band. Based on new set of Fourier transform spectra using various mixtures of CH3 F and N2, a multispectrum fitting procedure was used to retrieve N2 -broadening for 1189 transitions between 1105 and 1291 cm −1 . 899 transitions have been studied to model the J - and K -rotational quantum number dependences of the N2 -broadening coefficients in order to generate any transitions of CH3 F assuming no vibrational dependence. The accuracy of the retained N2 -broadening coefficients was estimated to be between 2–5%. These measurements have been compared with previous studies from the literature obtained for other bands of CH3 F. Comparison with the results obtained for similar empirical J - and K -rotational model applied to CH3 Cl, CH3 Br and CH3 F (this work) molecules is also presented. Graphical abstract: Image, graphical abstract